Comparing Impact of Two Resin Infiltration Systems on Microhardness of Demineralized Human Enamel after Exposure to Acidic Challenge - Alagha, Ebaa; Alagha, Mustafa Ibrahim (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study compared the impact of two resin infiltration systems on microhardness of demineralized enamel before and after an acidic challenge. MATERIALS AND METHODS: A total of forty human maxillary molar teeth were used in this study. Each tooth has 4 groups (four standardized windows onto each tooth). Group A1: Untreated sound enamel surface (positive control), Group A2: Artificially demineralized enamel surface (negative control), Group A3: Icon resin infiltrating to demineralized enamel, while Group A4: Single bond universal adhesive applied to the demineralized enamel surface. All teeth were immersed in a demineralizing solution. The groups (A3 and A4) were further subdivided into two subgroups according to acidic ethanol challenge Subgroup B1: Specimens tested before an acidic challenge and B2: Specimens tested after an acidic challenge. Vickers microhardness test was done for all groups. One-way analysis of variance (ANOVA) was used to study the difference between tested groups on mean microhardness within each group. Tukey’s post-hoc test was used for pair-wise comparison between the means when ANOVA test was performed, and the significance level was set at p ≤ 0.05. RESULTS: Icon resin infiltration and single bond universal adhesive showed significantly higher mean microhardness than negative control, but significantly lower mean microhardness than positive control. However, insignificant difference was found between icon and single bond universal adhesive. After the acidic challenge, icon resin infiltration showed significantly higher mean microhardness than negative control. However, single bond universal adhesive showed insignificant difference as compared to the negative control. CONCLUSION: After an acidic challenge, icon resin infiltration was more successful than single bond universal total-etch adhesive system in microhardness. RECOMMENDATION: Icon resin infiltration technique is a promising, noninvasive approach that prevents the progress of the carious lesion.